Quantifying variability in stable carbon and nitrogen isotope ratios within the skeletons of marine mammals of the suborder Caniformia. (October 2017) - Clark, Casey T.; Horstmann, Lara; Misarti, Nicole
Abstract: Stable isotope ratios of bone collagen are commonly used to investigate foraging and movement of human and animal populations. This technique is especially valuable for archaeological and paleoecological applications, as bones are among the few tissues that are commonly preserved in archaeological and assemblages. Selection of skeletal elements for stable isotope analysis is typically driven by sample sizes and convenience, with the assumption that each bone is equally likely to be representative of the entire skeleton. This study investigated the degree of variability in stable carbon and nitrogen isotope ratios (δ 13 C and δ 15 N) within the skeletons of individual marine mammals to determine whether any systematic differences in δ 13 C and δ 15 N exist among skeletal elements. We measured δ 13 C and δ 15 N in paired crania and mandibles from 11 Pacific walruses ( Odobenus rosmarus divergens ), as well as representative elements from the skeletons of three marine mammals: an adult ringed seal ( Pusa hispida, n = 10), a juvenile seal of the genus Phoca ( Phoca sp., n = 9), and an adult sea otter ( Enhydra lutris, n = 8). Differences among the walrus cranium/mandible pairs were not significant, mostly falling within analytical error. Variability across the skeletons of the seals and sea otter was greater, exceeding 1.0‰ in some cases. Hierarchical cluster analysis indicated systematic differences within all three skeletons, with the distal appendicular bones (metatarsal, phalanx, calcaneus) separating from the rest of the skeleton in the two seals, and the scapula and vertebra distinct from all other bones in the sea otter. Removing these bones from analysis greatly reduced overall variability in all three animals. Further study is required to determine whether the patterns observed in this study are consistent across individuals and taxa as sample sizes increase. Graphical abstract: Highlights: δ 13 C and δ 15 N variability within the skeletons of marine Caniformia were examined. Variability was typically < 1.0‰, but exceed this value in some cases. In seal skeletons, carpal/tarsal/phalanx grouped together, apart from other bones. In a sea otter skeleton, vertebra/scapula grouped together, apart from other bones. Removing these elements from analysis greatly reduced overall variability.